THE INFLUENCE OF DIFFERENT GROWING MEDIA ON THE GROWTH OF WATER SPINACH (IPOMEA REPTANS Poir) USING AQUAPONIC TECHNOLOGY - Sukma, Clarasita Renadevisari Marifel; Mardliyah, Auliya Tuhfatul; Handono, Fidela Nur Azizah; Nurhayati, Aprinia Dian (Universitas Medan Area, 2024)
This research aims to determine the best-growing medium to support the growth of water spinach plants using aquaponic technology. The study used a non-factorial Completely Randomized Design (CRD) method. There were four types of planting media treatments, namely, rockwool (control), cocopeat (P1), pasir malang (P2), and burnt husk (P3), there were five growth parameters observed (plant height (cm), number of leaves, stem diameter (mm), wet weight (gr), and leaf color) were monitored once a week starting from 7 HST to 28 HST. Data were analyzed using variance at a confidence level of 5% and continued with the Duncan test (DMRT) at a level of 5%. The results showed that the type of growing medium affects the growth of water spinach. pasir malang provided the best results for all plant parameters. However, it was not significantly different from burnt husk, except for stem diameter, where pasir malang differed significantly from the other treatments. Rockwool, pasir malang, and the burnt husk produced better and healthier leaf colors compared to cocopeat.